2002
DOI: 10.1023/a:1022965212971
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Circadian dynamics of rectal reactivity was studied in humans with regular and irregular rhythms of bowel evacuation function by chronoenterography. In individuals with regular rhythm of this function (stool 7 days per week) the acrophase of circadian rhythm of rectal reactivity was observed in morning hours, while in the daytime and evening and this parameter decreased almost 7-fold. In subjects with bowel arrhythmia (3-6 days with stool per week) rectal reactivity was inversed: 2-fold decreased in the mornin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Defection is an overt indication of colonic motility that shows daily rhythmicity, peaking in the active period. This has been reported in numerous species, including diurnal humans ( Rendtorff and Kashgarian, 1967 ; Heaton et al, 1992 ; Aschoff, 1994 ; Shemerovskii, 2002 ) and non-human primates ( Bernstein, 1964 ; Caton et al, 1996 ), birds ( Clarke, 1979 ; Rodriguez-Sinovas et al, 1994 ; Malek et al, 2020 ), dogs ( Hirabayashi et al, 2009 ), horses ( Piccione et al, 2005 ), camels ( Aubè et al, 2017 ), and sheep ( Piccione et al, 2005 ); and nocturnal rodents ( Gosling, 1979 ; Magot and Chevallier, 1983 ; Firpo et al, 2005 ; Hoogerwerf et al, 2010 ; de Azevedo et al, 2011 ; Platt et al, 2013 ; Allen and Johnson, 2018 ), foxes ( Klenk, 1971 ), antechinus ( Cowan et al, 1974 ), rabbit ( Jilge, 1974 ; Jilge and Hudson, 2001 ), hare ( Pehrson, 1983 ), and house musk ( Kobayashi et al, 2022 ). Some species, such as degu and the Mongolian gerbil that can show either diurnal or nocturnal activity patterns ( Refinetti, 2006 ) have a more constant defecation pattern ( Kenagy et al, 1999 ).…”
Section: Introductionmentioning
confidence: 53%
“…Defection is an overt indication of colonic motility that shows daily rhythmicity, peaking in the active period. This has been reported in numerous species, including diurnal humans ( Rendtorff and Kashgarian, 1967 ; Heaton et al, 1992 ; Aschoff, 1994 ; Shemerovskii, 2002 ) and non-human primates ( Bernstein, 1964 ; Caton et al, 1996 ), birds ( Clarke, 1979 ; Rodriguez-Sinovas et al, 1994 ; Malek et al, 2020 ), dogs ( Hirabayashi et al, 2009 ), horses ( Piccione et al, 2005 ), camels ( Aubè et al, 2017 ), and sheep ( Piccione et al, 2005 ); and nocturnal rodents ( Gosling, 1979 ; Magot and Chevallier, 1983 ; Firpo et al, 2005 ; Hoogerwerf et al, 2010 ; de Azevedo et al, 2011 ; Platt et al, 2013 ; Allen and Johnson, 2018 ), foxes ( Klenk, 1971 ), antechinus ( Cowan et al, 1974 ), rabbit ( Jilge, 1974 ; Jilge and Hudson, 2001 ), hare ( Pehrson, 1983 ), and house musk ( Kobayashi et al, 2022 ). Some species, such as degu and the Mongolian gerbil that can show either diurnal or nocturnal activity patterns ( Refinetti, 2006 ) have a more constant defecation pattern ( Kenagy et al, 1999 ).…”
Section: Introductionmentioning
confidence: 53%
“…Patients with chronic slow transit constipation have significantly reduced colonic pressure activity after waking up or food intake compared to healthy individuals [33]. A study by Shemerovskii et al found that healthy individuals have daily bowel movements in the morning between 6 am and noon, while those with irregular bowel habits have daily bowel movements only three to four times a week, predominantly between 8 pm and midnight [34]. Hence, the human colon has been naturally programmed to empty in the morning after awakening, and this biorhythm can potentially be altered by VC to achieve beneficial treatment effects in patients with chronic constipation [35].…”
Section: Discussionmentioning
confidence: 99%
“…Методом «Хроноэнтерографии» [4][5][6] обследовано 356 волонтёров (студенты-медики в возрасте 19-22 лет, 242 женщины). Кроме того, обследован 2501 медицинский работник в возрасте от 24 до 75 лет, 76% женщины с помощью анкетирования -1-страничный тест «Ритмы и здоровье».…”
Section: методика исследованияunclassified